A Comparison of the Short-term Outcomes of Three Flap Reconstruction Techniques Used After Beyond Total Mesorectal Excision Surgery for Anorectal Cancer. Issue 4 (April 2020) - Baird, Daniel L.H.; Pellino, Gianluca; Rasheed, Shahnawaz; Power, Kieran T.; Kontovounisios, Christos; Tekkis, Paris P.; Ramsey, Kelvin W.
Abstract : BACKGROUND: Surgery for advanced or recurrent pelvic malignancy can result in perineal defects that cannot be closed by wound edge approximation. Myocutaneous flaps can fill the defect and accelerate healing. No reconstruction has been proven to be superior to the others. OBJECTIVE: This study aimed to compare 3 flap procedures after beyond total mesorectal excision surgery. DESIGN: This is a retrospective analysis of a prospective database, according to the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) statement. SETTINGS: This study was performed at a tertiary hospital. PATIENTS: Consecutive series of patients who required flap reconstruction after beyond total mesorectal excision surgery between 2007 and 2016 were included. MAIN OUTCOME MEASURES: Short-term outcomes after oblique rectus abdominis flap vs vertical rectus abdominis flap vs inferior gluteal artery perforator flap reconstruction were evaluated. RESULTS: Included are 65 (59%) oblique rectus abdominis flap, 30 (27.3%) vertical rectus abdominis flap, and 15 (13.7%) inferior gluteal artery perforator flap outcomes. Sacrectomy was performed in 12 (18.5%), 10 (33.3%), and 8 (53.3%) patients ( p = 0.016). Preoperative radiotherapy was used in 60 (92.3%), 26 (86.7%), and 11 (73.3%) patients ( p = 0.11). Flap infection and dehiscence occurred in 7 (10.8%), 1 (3.3%), and 4 (26.7%) patients. There was an increased risk of flap complication with inferior gluteal artery perforator flap vs vertical rectus abdominis flap ( p = 0.036). Inferior gluteal artery perforator flap (OR, 6.26; p = 0.02) and obesity (OR, 4.96; p = 0.02) were associated with flap complications. Only complications of the oblique rectus abdominis flap decreased significantly over time ( p = 0.03). The length of stay and complete (R0) resection rate were not different between the groups. LIMITATIONS: This study was limited because of its retrospective nature and because it was conducted at a single center. CONCLUSIONS: The techniques appear comparable. The approaches should be considered complementary, and the choice should be individualized. See Video Abstract at http://links.lww.com/DCR/B141 . comparaciÓN DE RESULTADOS A CORTO PLAZO DE TRES TÉCNICAS DE RECONSTRUCCIÓN CON COLGAJO UTILIZADAS DESPUÉS DE LA CIRUGÍA DE ESCISIÓN MESORRECTAL TOTAL EXTENDIDA PARA EL CÁNCER ANORRECTAL: ANTECEDENTES: La cirugía para malignidad pélvica avanzada o recurrente puede provocar defectos perineales, que no pueden cerrarse por aproximación de los bordes de la herida. Los colgajos miocutáneos pueden llenar el defecto y acelerar la curación. Ninguna reconstrucción ha demostrado ser superior a las demás. OBJETIVO: Comparar tres procedimientos de colgajo después de una cirugía de escisión mesorrectal total extendida. DISEÑO: Análisis retrospectivo de una base de datos prospectiva, de acuerdo con la Declaración de Fortalecimiento de los informes de estudios observacionales en epidemiología. AMBIENTE CLÍNICO: Hospital de tercer nivel. PACIENTES E INTERVENCIONES: Series consecutivas de pacientes que requirieron reconstrucción con colgajo después de una cirugía de escisión mesorrectal total extendida entre 2007 y 2016. PRINCIPALES MEDIDAS DE VALORACIÓN: Resultados a corto plazo después del colgajo oblicuo recto abdominal versus colgajo vertical recto abdominal versus reconstrucción del colgajo perforador de la arteria glútea inferior. RESULTADOS: Se incluyen 65 (59%) colgajo oblicuo recto abdominal oblicuo, 30 (27.3%) colgajo vertical recto abdominal y 15 (13.7%) colgajo perforador de la arteria glútea inferior. Sacrectomía se realizó en 12 (18.5%), 10 (33.3%) y 8 (53.3%) pacientes respectivamente ( p = 0.016). La radioterapia preoperatoria se utilizó en 60 (92.3%), 26 (86.7%) y 11 (73.3%) ( p = 0, 11). La infección del colgajo y la dehiscencia ocurrieron en 7 (10.8%), 1 (3.3%) y 4 (26.7%). Hubo un mayor riesgo de complicación con el colgajo perforador de la arteria glútea inferior en comparación al colgajo vertical del recto abdominal (p = 0.036). El colgajo perforador de la arteria glútea inferior (OR 6.26, p = 0.02) y la obesidad (OR 4.96, p = 0.02) se asociaron con complicaciones del colgajo. Solo las complicaciones del colgajo oblicuo recto abdominal disminuyeron significativamente con el tiempo ( p = 0.03). La duración de la estancia hospitalaria y la tasa de resección completa (R0) no fue diferente entre los grupos. LIMITACIONES: Estudio retrospectivo en centro único. CONCLUSIONES: Las técnicas parecen comparables. Los enfoques deben considerarse complementarios y la elección individualizada. Consulte Video Resumen en http://links.lww.com/DCR/B141 . Abstract : Supplemental Digital Content is available in the text.